Anoctamin 2-chloride channels reduce simple spike activity and mediate inhibition at elevated calcium concentration in cerebellar Purkinje cells - Auer, Friederike; Taveras, Eliana Franco; Klein, Uli; Kesenheimer, Céline; Fleischhauer, Dana; Möhrlen, Frank; Frings, Stephan (PLOS ONE, 2021)
Modulation of neuronal excitability is a prominent way of shaping the activity of neuronal networks. Recent studies highlight the role of calcium-activated chloride currents in this context, as they can both increase or decrease excitability. The calcium-activated chloride channel Anoctamin 2 (ANO2 alias TMEM16B) has been described in several regions of the mouse brain, including the olivo-cerebellar system. In inferior olivary neurons, ANO2 was proposed to increase excitability by facilitating the generation of high-threshold calcium spikes. An expression of ANO2 in cerebellar Purkinje cells was suggested, but its role in these neurons remains unclear. In the present study, we confirmed the expression of Ano2 mRNA in Purkinje cells and performed electrophysiological recordings to examine the influence of ANO2-chloride channels on the excitability of Purkinje cells by comparing wildtype mice to mice lacking ANO2. Recordings were performed in acute cerebellar slices of adult mice, which provided the possibility to study the role of ANO2 within the cerebellar cortex. Purkinje cells were uncoupled from climbing fiber input to assess specifically the effect of ANO2 channels on Purkinje cell activity. We identified an attenuating effect of ANO2-mediated chloride currents on the instantaneous simple spike activity both during strong current injections and during current injections close to the simple spike threshold. Moreover, we report a reduction of inhibitory currents from GABAergic interneurons upon depolarization, lasting for several seconds. Together with the role of ANO2-chloride channels in inferior olivary neurons, our data extend the evidence for a role of chloride-dependent modulation in the olivo-cerebellar system that might be important for proper cerebellum-dependent motor coordination and learning.